EDUCATOR AND EDUCATION PERSONNEL PLANNING IN THE VIEW OF ISLAM - Fitriani, Fitriani; Mustofa, M. Lutfi (PT. Antis International Publisher, 2024)
General Background: The planning of educators and education personnel plays a critical role in the effectiveness of educational institutions, especially in ensuring that human resources are aligned with institutional goals. Specific Background: At the Institut Agama Islam Negeri (IAIN) Bone in South Sulawesi, Indonesia, this planning is essential to address the institution’s unique administrative and academic needs. Knowledge Gap: Despite its importance, there has been limited research that explores the detailed processes behind the planning of educational personnel, particularly in Islamic higher education institutions in Indonesia. Aims: This study aims to explore and describe the planning of educators and education personnel at IAIN Bone, using a qualitative approach to understand how institutional leaders coordinate and implement such plans. Results: The findings reveal that the planning process is comprehensive, involving an analysis of needs, problem identification, and data collection through leader coordination. Actions are executed based on Standard Operating Procedures (SOPs), and solutions are collectively formulated to serve as future references. Novelty: The research provides new insights into the structured, SOP-based planning methods used at IAIN Bone, highlighting a collaborative approach that involves multiple stakeholders, which has not been widely documented in previous studies on educational personnel planning. Implications: These findings underscore the importance of structured, needs-based planning in educational institutions, offering a model that other Islamic institutions in similar contexts could adapt to improve human resource management and institutional efficiency.